Kingdom Graph: Mengapa Gereja-Gereja di Iran Dan Tiongkok Berkembang Pesat walau dalam Tekanan atau Aniaya - Victor Christianto; Simon Simon (Jurnal Teologi Amreta (ISSN: 2599-3100))
Among the Pentecostal / Charismatic circles, a distinctive hermeneutic understanding has developed, which Menzies wrote in his book: This story is our story. This means an understanding that the story of the early church that we read in the Acts of the Apostles is also the story of the churches today in various places, which also experienced various pressures and persecutions. This is especially so in Iran and China, but what is strange is that the seeds of God's Word, which seemed to fall on rocky ground, did not immediately die out, but instead found unique ways to grow. This article notes some things that churches in other places need to listen to and learn about their tenacity and perseverance and zeal. In the second part, the authors present a graph model to understand church growth as an endogenous process. We hope that these observations and mathematical models are useful for church leaders in developing a more dynamic ecclesiology.